A woman praised by women is better than a woman praised by seven men - Loader, James Alfred (HTS teologiese studies, 2004)
The title, a parody on Ruth 4:15bb and Proverbs 31:28, counterposes the motif of praise in the final scene of what is probably the opus classicum for the foregrounding of women in the Old Testament with the same motif in a text notorious for praising women into subservience. After a short presentation of the text of Ruth 4:13-17, its main ideas and compositional relationships with the rest of the Book, the focus falls on the praise of the women of Bethlehem, its presuppositions, logic, use of terms and the role of its speakers in the story. It is concluded that a non-feminist, intentional reading highlights the critical perspective of women in the narrative, which means that the gist of mainstream feminist readings of the Ruth story is corroborated even from a perspective independent of feminist hermeneutic.